A criterion of elementary divisor domain for distributive domains - Bokhonko, V.; Zabavsky, B.V. (Algebra and Discrete Mathematics, 2017)
In this paper we introduce the notion of the neat range one for Bezout duo-domains. We show that a distributive Bezout domain is an elementary divisor domain if and only if it is a duo-domain of neat range one.